2020
DOI: 10.1109/tasc.2020.2981269
|View full text |Cite
|
Sign up to set email alerts
|

Test Results of the First Two Full-Length Prototype Quadrupole Magnets for the LHC Hi-Lumi Upgrade

Abstract: The future high luminosity (Hi-Lumi) upgrade of the Large Hadron Collider (LHC) at CERN will include eight (plus two spares) 8.4 m-long cryostatted cold masses which will be components of the triplets for two LHC insertion regions. Each cold mass will consist of two 4.2 m long Nb3Sn high gradient quadrupole magnets, designated MQXFA, with aperture 150 mm and operating gradient 132.6 T/m, for a total of twenty magnets. Before assembling and testing the final cold masses at Fermilab, the twenty component quadrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…The test of the first MQXFA prototype (MQXFAP1) [8], performed at BNL Vertical Test Facility, was stopped after detection of a coil-to-ground short when magnet training had almost reached 17.5 kA. Test data analysis and autopsy [7] showed that this short had been caused by a series of issues, which we summarize in chronological order: 1) a coil (QXFP5) used in this magnet had an experimental S2-glass cloth (provided by a new vendor and with a denser fabric than all cloths previously used) on its outer surface that resulted in a non-conforming epoxy impregnation due to dry spots; 2) during the first quench, the test facility burst valve ruptured forcing a thermal cycle; 3) at room temperature heater-to-coil high-voltage withstand (Hipot) tests were performed at the pre-cooldown values (2.5 kV) and one heater of coil QXFP5 failed; 4) Hipot tests were repeated on the failed heater to assess its reduced insulation strength but ended up causing further degradation; 5) after cooldown the failed QXFP5 heater was found to be shorted to the coil and was disconnected from the heater firing unit and from ground.…”
Section: Lessons Learned About Electrical Qc Testsmentioning
confidence: 99%
“…The test of the first MQXFA prototype (MQXFAP1) [8], performed at BNL Vertical Test Facility, was stopped after detection of a coil-to-ground short when magnet training had almost reached 17.5 kA. Test data analysis and autopsy [7] showed that this short had been caused by a series of issues, which we summarize in chronological order: 1) a coil (QXFP5) used in this magnet had an experimental S2-glass cloth (provided by a new vendor and with a denser fabric than all cloths previously used) on its outer surface that resulted in a non-conforming epoxy impregnation due to dry spots; 2) during the first quench, the test facility burst valve ruptured forcing a thermal cycle; 3) at room temperature heater-to-coil high-voltage withstand (Hipot) tests were performed at the pre-cooldown values (2.5 kV) and one heater of coil QXFP5 failed; 4) Hipot tests were repeated on the failed heater to assess its reduced insulation strength but ended up causing further degradation; 5) after cooldown the failed QXFP5 heater was found to be shorted to the coil and was disconnected from the heater firing unit and from ground.…”
Section: Lessons Learned About Electrical Qc Testsmentioning
confidence: 99%
“…MQXFAP1a was tested in the BNL vertical test facility and reported in [13] and [14]. The magnet experienced thermal cycles after the first and third quenches due to issues with the cryogenic system [13]. The magnet initially trained quicklyit had the highest first quench of the MQXF magnets to date, and took only 9 quenches to reach nominal current.…”
Section: B Mqxfap1 and Mqxfap2 Preload Targetsmentioning
confidence: 99%
“…The magnet had a first quench at 13.3 kA and reached 15 kA in 10 quenches, which were followed by detraining quenches. The training performance of the magnet is reported in [13] and [14]. All coils participated in the quenches, but the magnet was not able to reach the nominal current.…”
Section: Mqxfap2 Test Campaign 1) Low Training Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Extensive quench protection studies were performed on various 1.2 m long model magnets [18]- [25], which allowed defining protection parameters [26], [27]. The first 4.0 m long prototype magnet, named MQXFAP1, was tested at the Brookhaven National Laboratory (BNL) test facility in stand-alone configuration [28], [29].…”
mentioning
confidence: 99%